138k views
0 votes
Solve this quadratic equation using the quadratic formula. 5 - 10x - 3x2 = 0

2 Answers

6 votes

Answer:

x = (-5 ± 2√10) / 3

Explanation:

5 − 10x − 3x² = 0

Write in standard form:

-3x² − 10x + 5 = 0

Solve with quadratic formula:

x = [ -b ± √(b² − 4ac) ] / 2a

x = [ -(-10) ± √((-10)² − 4(-3)(5)) ] / 2(-3)

x = [ 10 ± √(100 + 60) ] / -6

x = (10 ± 4√10) / -6

x = (-5 ± 2√10) / 3

7 votes

Explanation:


5 - 10x - 3 * 2 = 0


multiply \: the \: numbers \\ \\ 5 - 10 x- 6 = 0


collect \: like \: terms \\ \\ 5 - 6 - 10x


- 1 - 10x = 0


- 10x = 1


divide \: both \: sides \: of \: the \: equation \: by \: - 10


x = - \ (1)/(10)


alt \: form \: = \\ \\ = 0.1 \\ x = - 10 {}^( - 1)

Hope this helps. :)

User Scott Storch
by
4.5k points